CUSTOMIZED PEEK TEMPORARY ABUTMENT FOR SINGLE MAXILLARY ANTERIOR IMPLANT - Andi Bawono, Chandra; Arifianti, Isti (Fakultas Kedokteran Gigi Unjani, 2024)
The use of dental Implants in Indonesia has increased significantly. Public knowledge and demand for dental implant treatments are growing. The public’s need to replace missing teeth with removable dentures or bridges gradually shifting towards dental implant. The aesthetic needs for dental implant, especially in the anterior region are highly desired by patients. However, this is often not achieved due to several factor, one of it was the non-optimal emergence profile of the implant supra structure. A deep understanding of the gingival tissues in relation to implants to achieve maximum esthetics is utmost importance. This case report presented the treatment with an implant using a PEEK temporary abutment as a custom healing abutment The use of customized temporary abutment as a healing abutment could provide an effective method to enhance esthetic and guide tissue response during the healing phase, so that the aesthetic could be achieved. DOI : 10.54052/jhds.v4n2.p117-126